The Case for a 21st Century Wilderness Ethic. Issue 2 (3rd May 2020) - Petersen, Brian; Hultgren, John
ABSTRACT: Past debates surrounding wilderness have not led to constructive dialogue but instead have created a rift between dueling sides. Far from academic, this debate has important ethical, policy, and practical implications. We outline out the major fault lines of the debate between wilderness realists and constructivists and also identify common ground between them. From this starting point, we offer three potential bridges between them and conclude by proposing a preliminary vision of a 21 st Century wilderness ethic focused on social-ecological connection, re-commoning, and social justice. Returning to the 'great wilderness debate' can lead to a synthesis of the realist and constructivist positions and a renewed wilderness ethic in an era of neoliberalism, hyper-nationalism, and intensified environmental crises.